Nutritional changes in patients with locally advanced head and neck cancer during treatment. (August 2017) - Arribas, L.; Hurtós, L.; Taberna, M.; Peiró, I.; Vilajosana, E.; Lozano, A.; Vazquez, S.; Mesia, R.; Virgili, N.
Highlights: Nutritional status in patients with advanced head and neck squamous cell carcinoma deteriorates during radiotherapy despite an intensive nutritional support. Induction chemotherapy may help to improve nutritional status by ameliorating the symptoms that limit the oral intake. Abstract: Objective: The purpose of the study is to evaluate changes in body composition and nutritional status that occur throughout the oncological treatment in head and neck cancer patients. Methods: A prospective cohort observational study in patients diagnosed with head and neck squamous cell carcinoma (HNSCC) that underwent treatment with induction chemotherapy (iCT) followed by chemoradiotherapy or bioradiotherapy were invited to participate. All patients had dietetic counseling from the diagnosis and a close monitoring throughout the treatment implementing nutritional support as needed. Results: From June 2011 until October 2012, 20 patients were included. Nutritional and anthropometric parameters were collected at diagnosis, post iCT, after radiotherapy, 1 and 3 months post radiotherapy. According to Patient Generated Subjective Global Assessment, 30% of patients were malnourished at diagnosis. After iCT there was an increase in weight, body mass index (BMI) and fat free mass (FFM) with almost complete improvement in dysphagia and odynophagia. Nevertheless a significant nutritional deterioration (p = 0.0022) occurred at the end of radiotherapy with 95% of patients becoming severe or moderate malnourished. Nutritional parameters such as weight, BMI and hand grip strength also decrease significantly during treatment. Conclusions: Despite an intensive nutritional support from the diagnosis throughout the oncological treatment in advanced HNSCC cancer patients, nutritional status deteriorates during radiotherapy. Our findings suggest that iCT may help improve nutritional status by ameliorating the symptoms that limit the oral intake. This improvement in the nutritional status could contribute to minimize further deterioration. Further investigations are needed involving novel approaches to avoid nutritional deterioration.